Altering endocannabinoid neurotransmission at critical developmental ages: impact on rodent emotionality and cognitive performance - Trezza, Viviana; Campolongo, Patrizia; Manduca, Antonia; Morena, Maria; Palmery, Maura; Vanderschuren, Louk; Cuomo, Vincenzo (Frontiers in Behavioral Neuroscience, 2012)
The endocannabinoid system shows functional activity from early stages of brain development: it plays an important role in fundamental developmental processes such as cell proliferation, migration and differentiation, thus shaping brain organization during pre- and postnatal life. Cannabis sativa preparations are among the illicit drugs most commonly used by young people, including pregnant women. The developing brain can be therefore exposed to cannabis preparations during two critical periods: first, in offspring of cannabis-using mothers through perinatal and/or prenatal exposure; second, in adolescent cannabis users during neural maturation. In the last decade, it has become clear that the endocannabinoid system critically modulates memory processing and emotional responses. Therefore, it is well possible that developmental exposure to cannabinoid compounds induces enduring changes in behaviors and neural processes belonging to the cognitive and emotional domains. We address this issue by focusing on rodent studies, in order to provide a framework for understanding the impact of cannabinoid exposure on the developing brain.